UPAYA MENINGKATKAN PEMAHAMAN MATERI PERADABAN EMAS DINASTI ABBASIYAH MELALUI METODE JIGSAW DIKELAS VIII MADRASAH TSANAWIYAH RAUDLATUL ULUM NGIJO KARANG PLOSO - Safirah Nurdin; Anwar Sa’dullah; Fita Mustafida (VICRATINA, 2020)
This types of research aims to describe and find out how the application and improvement of the jigsaw method in Mts. Raudlatul Ulum Ngijo. The problem that often occurs is studets feel bored and less active in the learning process of students less enthusiastic, atmosphere becomes rigid and the methods used are still using convetional methods. With the application of the learning system jigsaw method, students are expected to be more creative and active in accepting the learning process so that students can improve understanding of learning in accordance wit the objectives of Education. This research is a Class Action Research (CAR), this data collection technique is to use observation, interviews, tests, and documentation.